Управління соціально-економічним розвитком об’єднаних територіальних громад - Корчинська, О. О.; Korchynska, O. (Видавництво Львівської політехніки, 2019)
Досліджено реформи децентралізації в Україні, розглянуто питання, які стосуються управління соціально-економічного розвитку територій об’єднаних громад. Розкрито питання соціально-економічного розвитку, теоретичні основи об’єднаних територіальних громад та принципи їх створення, а також проаналізовано відповідну законодавчо-нормативну базу України. На основі проведеного дослідження визначено напрями підвищення соціально-економічного розвитку об’єднаної територіальної громади з врахуванням особливостей функціонування: ресурсного потенціалу та людського капіталу.

The article states that the reform of local self-government and territorial organization of power, is the creation of united territorial communities in Ukraine on the basis of decentralization, conceptual principles of which were approved in 2014, and practical implementation began in 2015, was among the most effective and significant proclaimed strategic reforms. Decentralization reform aims at creating a modern and modern system of local self-government in Ukraine based on European values of local democracy development, empowering territorial communities with the powers and resources that will provide local economic development, providing high quality and accessible public services to the population. The role of united territorial communities in ensuring the interests of citizens in all spheres of life in their respective territories should be key. Decentralization in government can be seen as a solution to problems such as the economic downturn, the inability of the government to finance services and their overall decline in productivity, the inability to meet the demands of the people in local government, and the weakening of public sector legitimacy. The process of decentralized governance refers to the restructuring or reorganization of power in order to create a shared system of responsibility between central, regional and local levels of governance in accordance with the principle of subsidiarity, which will increase the overall quality and efficiency of the management system, while enhancing the credibility and capacity of the united territorial communities. Decentralization and local governance are essential components of a democratic society that provides an enabling environment in which decision-making and service delivery can be brought closer to the local population. It is worth noting that the decentralization reform in Ukraine has addressed a number of such problems: insufficient quality and accessibility of public, municipal services due to the lack of sufficient resources, resources and powers by local authorities; insufficient availability of local self-government funds, which leads to poor and emergency condition of thermal, sewerage, water supply networks and housing stock and leads to the risk of man-made disasters; the complex demographic situation in most of the united territorial communities, namely: aging of the population, depopulation of rural areas and mono-functional cities; the inconsistency of local socio-economic development policies and strategies for the future with the real interests of local communities; excessive centralization of the powers of the executive authorities and financial and material resources; removal of local self-government from land issues, increasing social tension among rural population due to the lack of ubiquity of local selfgovernment. The social transformations that have taken place in Ukraine in recent years have led to a significant strengthening of the role and importance of the regions, and their level of development has largely determined the development of the country as a whole. The process of decentralization, reform, creation of the union territorial communities gradually lead to changes in the structure, procedures and practices of governance, which will allow the state bodies to be closer to the citizens of society and to better understand their problems, needs and desires.
Management of socio-economic development of united territorial communities
Keywords: децентралізація; об’єднана територіальна громада; соціально-економічний розвиток; державне управління; ресурсний потенціал; decentralization; united territorial community; socio-economic development; public administration; resource potential; 338.26